Training in-service physical educators to improve class time management. (Formar a profesores de Educaciόn Fίsica en la mejora de la administración del tiempo de clase.) - Olga Vasiliadou; Vassiliki Derri; Nikiforos Galanis; Kyriaki Emmanouilidou (Ramón Cantó Alcaraz, 2009)
Abstract The purpose of the present study was to examine the effect of a short-term training program οn physical education time management, in elementary school. Thirty-two physical educators were randomly divided into experimental and control group. Each teacher taught six lessons (two for pre-test, two for post-test and two for retention test). After the pre-test, the experimental group attended a training program which included a two-hour lecture with emphasis on how to effectively manage the allotted class time, and a two-hour practicum, supervised by the researcher. Then, both groups were post- and retention tested. For the evaluation of class time management, the form Time Management (Graham, 2001) was used. Multivariate analysis of variance with repeated measures and analysis of covariance were used for data analysis. Results showed that physical educators in the experimental group learned to increase student activity time, and managed student waiting time significantly better than those in the control group which, on the other hand, managed significantly better the time allotted to provide instructions. It is concluded that a short but focused training can significantly influence class time management, an important criterion of teaching effectiveness. Resumen Este estudio ha perseguido analizar qué efecto tiene la aplicación de un programa educativo corto en la administración del tiempo en Educación Física en Enseñanza Primaria. Para ello, treinta y dos profesores fueron divididos aleatoriamente en dos grupos: experimental y control. Cada profesor impartió seis clases (dos pre-test, dos post-test y dos de retención). Tras el pre-test, el grupo experimental siguiό un programa sobre cόmo administrar eficazmente el tiempo de clase, con dos horas de lectura y un prácticum de dos horas supervisado por el investigador. Todo ello fue seguido de un post-test y retenciόn de pruebas por ambos grupos, para lo cual se utilizó el formulario de Administraciόn de Tiempo (Graham, 2001). Los análisis de la variaciόn multivariante para las medidas repetidas y de la covariaciόn demostraron que los profesores del grupo experimental aumentaron el tiempo de actividad del estudiante y manejaron su tiempo de espera significativamente mejor que el grupo de control, el cual por su parte manejό significativamente mejor el tiempo asignado para proporcionar instrucciones. Puede concluirse que un programa debidamente enfocado puede influir significativamente en la administración de tiempo de la clase, un criterio importante de eficacia en la enseñanza.